Towards a unified scheme of cortical lamination for primary visual cortex across primates: insights from NeuN and VGLUT2 immunoreactivity - Balaram, Pooja; Kaas, Jon H. (Frontiers in Neuroanatomy, 2014)
Primary visual cortex (V1) is clearly distinguishable from other cortical areas by its distinctive pattern of neocortical lamination across mammalian species. In some mammals, primates in particular, the layers of V1 are further divided into a number of sublayers based on their anatomical and functional characteristics. While these sublayers are easily recognizable across a range of primates, the exact number of divisions in each layer and their relative position within the depth of V1 has been inconsistently reported, largely due to conflicting schemes of nomenclature for the V1 layers. This conflict centers on the definition of layer 4 in primate V1, and the subdivisions of layer 4 that can be consistently identified across primate species. Brodmann’s (1909) laminar scheme for V1 delineates three subdivisions of layer 4 in primates, based on cellular morphology and geniculate inputs in anthropoid monkeys. In contrast, Hässler’s (1967) laminar scheme delineates a single layer 4 and multiple subdivisions of layer 3, based on comparisons of V1 lamination across the primate lineage. In order to clarify laminar divisions in primate visual cortex, we performed NeuN and VGLUT2 immunohistochemistry in V1 of chimpanzees, Old World macaque monkeys, New World squirrel, owl, and marmoset monkeys, prosimian galagos and mouse lemurs, and nonprimate, but highly visual, tree shrews. By comparing the laminar divisions identified by each method across species, we find that Hässler’s (1967) laminar scheme for V1 provides a more consistent representation of neocortical layers across all primates, including humans, and facilitates comparisons of V1 lamination with nonprimate species. These findings, along with many others, support the consistent use of Hässler’s laminar scheme in V1 research.